Penanaman Budaya Literasi Membaca dan Numerasi Melalui Penyuluhan Wawasan Bacaan dan Tahfizh Al-Quran Serta Lomba PHBI - Mohamad Riyadi; Anggar Titis Prayitno; Daswa; Dilla Dzahrotul Aeni; Eva Fauziyah (Transformatif : Jurnal Pengabdian Masyarakat, 2024)
Reading literacy and numeracy literacy are skills that play an essential role in facing the challenges of the 21st century. This service aims to instill a culture of reading literacy and numeracy literacy in teachers, parents and students who take part in Al-Quran Reading and Tahfizh Program activities at Irmas Baeturrahmah, Kalibuntu Village, Regency Cirebon. Based on observations and interviews, there needs to be activities that can increase insight into reading and tahfizh Al-Quran in the form of counseling and can increase reading literacy and numeracy literacy among students in the form of competitions. The results of the service show that counseling provides motivation to improve learning of the Al-Quran and competitions can be held with high public interest.